CONCEPTUAL-THEORETICAL BASIS OF THE DEVELOPMENT OF STRATEGIC PROVISIONS OF MACROECONOMIC SYSTEMS - Марич, Максим; Dubyna, Maksym (My University, 2021)
The purpose of the scientific work is to study and analyze the conceptual and theoretical basis for the development of strategic principles of macroeconomic systems. The research used general economic and specific methods of scientific knowledge, including: formalization, abstraction, dialectical, decomposition, monographic, analysis and synthesis, generalizations, observations, comparisons and others. According to the results of research, the authors proposed the concept of systemogenesis of the functioning of systems of different nature. Scientists have presented an ontological consistency between such scientific definitions as paradigm, doctrine, concept, strategy and tactics.
Keywords: Strategic principles; Strategy; Paradigm; Doctrine; Macroeconomic system